Seasonal variations in Circumpolar Deep Water intrusions into the Ross Sea continental shelf - Wang, Yufei; Zhou, Meng; Zhang, Zhaoru; Dinniman, Michael S. (Frontiers in Marine Science, 2023)
Intrusions of the warm and nutrient-rich Circumpolar Deep Water (CDW) across the Ross Sea shelf break play an important role in providing heat for ice shelf basal melting and setting the physical environment for biochemical processes. Several mechanisms driving CDW intrusions into the Ross Sea were proposed such as mesoscale eddies, tidal rectification, and interactions between Antarctic Slope Current (ASC) and topographic features. The seasonal variations in the poleward transport of CDW are investigated using ERA-Interim wind data and a Ross Sea circulation model based on the Regional Ocean Modeling System (ROMS) between September 1999 and September 2014. The analyses focus on the currents along the shelf break and deep troughs on the Ross Sea shelf and discuss the wind-driven Ekman pumping in both shelf and adjacent open ocean regions. The results reveal that the poleward intrusions generally move up onto the continental shelf along the eastern flanks of deep troughs. Seasonal variations of the ocean surface stress torque exerted by wind and sea ice in the offshelf area are correlated with CDW intrusions. The maxima of CDW intrusions usually occur in austral summer. There is a significant temporal correlation on the seasonal time scale between the onshelf intrusions in deep troughs in the western Ross Sea shelf and poleward Sverdrup transports in the adjacent offshelf open ocean driven by Ekman pumping. The analysis of ocean surface stress fields also indicates that the vorticity fluxes through Ekman pumping are in favor of southward and northward transports in the eastern and western parts of the Ross Sea, respectively. The relationships between currents, CDW intrusions and ocean surface stress fields imply the importance of air-sea interactions and potential climate change to the environment in the Ross Sea.